Digital Transformation Of Customs In Indonesia’s Customs System - Hidayah, Nenden Restu; Susena, Karona Cahya; Rahmadania, Della (Social Sciences Journal, 2025)
Digital transformasi in Indonesia’s cusoms system is a strategic step to improve efficiency, transparency, and accuracy in customs processes. The manual system previously used often faced challenges such as complex bureaucracy, vulnerability to human erors, and slow data processing. This study aims to explore the impact od digital transformation on the performance of customs in Indonesia, particularly in accelerating service processes, reducing potential irregularities, and echancing trust among business actors. The results indicate that the implementation of technologies such as e-customs, digital surveillance systems, and automation of customs documents significantly reduces service time, improves monitoring systems for imported and exported goods, and increases state revenue from this sector. However, this transformation also faces challenges such as infrastructure readiness, workforce training, and data security. Therefore, strong collaboration between the government, businesses, and socienty is necessary to ensure the successful implementation of digital transformation in the customs system. This study contributes to understanding the importance of digitization in supporting efficiency and transparency in the customs sector in Indonesia.